Difference Method of General Schemes with Intrinsic Parallelism for One-dimensional Quasilinear Parabolic Systems with Bounded Measurable Coefficients (Journal of Partial Differential Equations, 1999)
The difference method of the general finite difference schemes with intrinsic parallelism for the boundary value problem of the quasilinear parabolic system is studied without assuming heuristically that the original boundary value problem has the unique smooth vector solution.
Keywords: Difference scheme; intrinsic parallelism; quasilinear parabolic system; convergence; stability